2017
DOI: 10.1002/jmri.25685
|View full text |Cite
|
Sign up to set email alerts
|

Longitudinal quantitative MRI assessment of cortical damage in multiple sclerosis: A pilot study

Abstract: 1 Technical Efficacy: Stage 1 J. Magn. Reson. Imaging 2017;46:1485-1490.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
21
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
7
1
1

Relationship

4
5

Authors

Journals

citations
Cited by 21 publications
(25 citation statements)
references
References 35 publications
(65 reference statements)
4
21
0
Order By: Relevance
“…28 The FCD voxels were removed from the T 2 maps to exclude FCD-associated changes from the analysis. To reduce partial volume effects with cerebrospinal fluid (CSF) and WM, T 2 values were sampled in the central 20% of the cortex 29 and saved in surface datasets.…”
Section: Segmentation and Data Analysismentioning
confidence: 99%
“…28 The FCD voxels were removed from the T 2 maps to exclude FCD-associated changes from the analysis. To reduce partial volume effects with cerebrospinal fluid (CSF) and WM, T 2 values were sampled in the central 20% of the cortex 29 and saved in surface datasets.…”
Section: Segmentation and Data Analysismentioning
confidence: 99%
“…1 Modern magnetic resonance imaging (MRI) techniques and immunohistochemical studies have revealed neuronal damage in early stages of the disease course of patients with clinically isolated syndrome (CIS) or relapsing-remitting multiple sclerosis (RRMS). [2][3][4] Based on the apparent molecular mass of the mammalian subunits, three major subunits of neurofilament have been defined: light (65−70 kDa), medium (140-160 kDa) and heavy chain (200-220 kDa). Neurofilament light chain (NfL) has been studied most extensively and an association with acute neuro-axonal damage was demonstrated for NfL which is elevated in CSF during all stages of multiple sclerosis (MS) with a heightened (10 times) increase in times of acute relapses.…”
Section: Introductionmentioning
confidence: 99%
“…Quantitative multi-parameter mapping (MPM) is an excellent example, whereby four quantitative maps [proton density (PD), magnetization transfer saturation (MT), longitudinal relaxation rate (R1 = 1/T1), and transverse relaxation rate (R2 * = 1/T2 * )] of the whole brain can be measured in a scan time of around 20 min (Weiskopf et al, 2013). These maps are sensitive to microstructural tissue properties of high clinical relevance, such as myelin and iron content (Weiskopf et al, 2015), and have been shown to be sensitive to pathology, for example in multiple sclerosis (Jurcoane et al, 2013;Gracien et al, 2017;Lommers et al, 2019) and spinal cord injury (Grabher et al, 2015). Despite the high validity of MPM (Weiskopf et al, 2013;Leutritz et al, 2020), the widely used standard MPM protocol with 1 mm resolution (Weiskopf et al, 2013;Callaghan et al, 2014;Grabher et al, 2015;Ziegler et al, 2018;Lommers et al, 2019;Leutritz et al, 2020;Taubert et al, 2020) has a relatively long acquisition time, limiting its translational potential (Bagnato et al, 2020).…”
Section: Introductionmentioning
confidence: 99%